(untitled) (Journal of actual problems of jurisprudence, 2019)
This article focuses on the concept and conditions of the commission to real estate. Real estate is one of the foundations of the functioning of any economic system. Therefore, the optimal organization of real estate turnover is one of the important problems in the field of legal policy. Legal regulation of relations connected with immovable property, plays a leading role. As citizens deal with the real estate owned by them have never received such a scale as it is now. Key words: real estate objects of civil law, the legal regime of the real estate transaction, land, registration of rights.